HF-ND-PB ISOTOPE EVIDENCE FROM PERMIAN ARC ROCKS FOR THE LONG-TERM PRESENCE OF THE INDIAN-PACIFIC MANTLE BOUNDARY IN THE SW PACIFIC - Nebel O.; Münker C.; Nebel-Jacobsen Y.J.; Kleine T.; Mezger K.; Mortimer N. (My University, 2007)
Trace element and initial Hf-Nd-Pb isotopic composition of a series of late Paleozoic arc rocks from South Island, New Zealand show evidence for the presence of Indian-type mantle in the Permian SW Pacific. The trace element budget points to a fluid-dominated arc setting such that Pb isotope compositions for both the volcanic and intrusive rocks were controlled by addition of fluids derived from the subducted slab to the mantle wedge. Relatively unradiogenic initial 207Pb/204Pb ratios indicate only a negligible contribution of pelagic sediments to the subduction component. Initial 208Pb/204Pb vs. 206Pb/204Pb co-variations therefore indicate that the subduction component originates from subducted oceanic crust having a Pacific-type composition. In contrast, Hf-Nd isotope correlations, corrected for slab fluid addition, reveal an Indian-type signature for the mantle wedge. Thus, the results indicate contribution of material from both Pacific- and Indian-type mantle sources to the island arc melts. From the source variability in Hf-Nd-Pb isotopes, it is therefore evident that a mantle domain boundary was present beneath the Permian Brook Street arc, similar to the prominent present-day isotope mantle boundary in the Earth's upper mantle, which can be traced along the western Pacific rim. These observations provide strong support that the isotopically defined mantle boundary between Indian and Pacific-type mantle was present in the SW Pacific since at least the late Permian. The existence of this boundary implies that convection cells of the Pacific and Indian mantle reservoirs co-existed in close proximity and yet remained distinct and isolated from each other since at least the late Permian. These results provide strong indirect evidence for the absence of significant chemical exchange between neighboring convecting regimes, at least for the approximate duration of one mantle overturn. Applying these distinct isotope features to the Permian plate tectonic configuration, the subduction polarity of the Brook Street arc was facing westwards, towards the active SE Gondwana margin. © 2006 Elsevier B.V. All rights reserved.
Keywords: BROOK STREET; HF-ND CO-VARIATIONS; INDIAN-TYPE MANTLE; MANTLE CONVECTION; Permian; Paleozoic::Permian; Палеозой::Пермская